2003
DOI: 10.1007/s00299-003-0574-0
|View full text |Cite
|
Sign up to set email alerts
|

Stable genetic transformation of Vigna mungo L. Hepper via Agrobacterium tumefaciens

Abstract: Vigna mungo is one of the large-seeded grain legumes that has not yet been transformed. We report here for the first time the production of morphologically normal and fertile transgenic plants from cotyledonarynode explants inoculated with Agrobacterium tumefaciens carrying binary vector pCAMBIA2301, the latter of which contains a neomycin phosphotransferase (nptII) gene and a b-glucuronidase (GUS) gene (uidA) interrupted with an intron. The transformed green shoots, selected and rooted on medium containing ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…Prolonged incubation of shoots in root induction media resulted in the ageing which had a negative effect on normal growth and seed yield (Ghosh et al 2017). Though there are reports of various direct rooting protocols in black gram (Saini et al 2002;Muruganatham et al 2005;Harisaranraj 2008;Adlinge et al 2014), those protocols lack detailed information about the number of roots produced per explant and root length. Direct rooting protocol in solidified MS media supplemented with IBA, IAA and NAA was tried in black gram but most of the protocols required at least 12-14 days for obtaining well developed healthy elongated roots with low success rate in plant establishment in the soil during the hardening procedure (Gill et al 1987;Ignacimuthu et al 1997;Eapen et al 1998;Ignacimuthu and Franklin 1999;Franklin et al 2000;Tyagi et al 2001;Agnihotri et al 2001;Villiers et al 2008;Shariful et al 2010;Adlinge et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prolonged incubation of shoots in root induction media resulted in the ageing which had a negative effect on normal growth and seed yield (Ghosh et al 2017). Though there are reports of various direct rooting protocols in black gram (Saini et al 2002;Muruganatham et al 2005;Harisaranraj 2008;Adlinge et al 2014), those protocols lack detailed information about the number of roots produced per explant and root length. Direct rooting protocol in solidified MS media supplemented with IBA, IAA and NAA was tried in black gram but most of the protocols required at least 12-14 days for obtaining well developed healthy elongated roots with low success rate in plant establishment in the soil during the hardening procedure (Gill et al 1987;Ignacimuthu et al 1997;Eapen et al 1998;Ignacimuthu and Franklin 1999;Franklin et al 2000;Tyagi et al 2001;Agnihotri et al 2001;Villiers et al 2008;Shariful et al 2010;Adlinge et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The Agobacterium mediated genetic transformation of Vigna mungo has so far been reported with Gus as a reporter gene and a selectable marker gene using the binary vector pCAMBIA 2301 and documented the presence of these genes by histohemical assay, PCR and Southern analysis (Karthikeyan et al 1996;Saini et al 2002;Saini and Jaiwal 2005;Saini and Jaiwal 2007;Acharjee et al 2012;Sainger et al 2015). Organogenesis from the embryonic axis triggering adventitious shoots after correct combination of hormone concentration, in vitro selection with optimum concentration of antibiotic kanamycin monosulphate and rooting are crucial to genetic transformation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the optimisation of in vitro propagation tools and advancements in genetic engineering techniques, the first transgenic crop was developed three decades ago (Eapen, ). Since then, the use of genetic transformation has been reported in most crops, including pulses, such as Vigna unguiculata (Popelka et al ., ), Vigna mungo (Saini et al ., ), Cicer arietinum (Fontana et al ., ), Cajanus cajan (Geetha et al ., ), Vicia faba (Ramsay & Kumar, ) and Pisum sativum (Schroeder et al ., ). Biochemical studies on pulses confirmed that lectins, the sugar‐binding proteins normally found in the seeds are involved in plant defence mechanisms against bruchids (Chrispeels & Raikhel, ; Peumans & Van Damme, ).…”
Section: Biotechnological Approachesmentioning
confidence: 99%
“…In blackgram, improved in vitro regeneration systems and genetic transformations by Agrobacterium tumefaciens have been recently developed. Saini et al 50 reported an efficient method of plant regeneration via direct multiple shoot organogenesis from cotyledonarynode explants together with an optimal selection system. The authors also described conditions for establishing an A. tumefaciens-based transformation protocol for the successful production of transgenic blackgram.…”
Section: Gene Transformation In Mungbean and Blackgrammentioning
confidence: 99%